PELAKSANAAN KEGIATAN EKSTRAKURIKULER TENIS MEJA DI SMA NURUL FALAH KOTA PEKANBARU DITINJAU DARI MINAT SISWA-SARANA DAN PRASARANA - Ary Wirata Kardi; Agus Sulastio; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Implementation of Table Tennis Extracurricular Activities at SMA Nurul Falah Pekanbaru City in terms of Student Interests – Facilities and Infrastructure. This research started from various information obtained about the implementation of table tennis extracurricular activities at SMA Nurul Falah Pekanbaru City which were not carried out as expected, many factors that influenced these extracurricular activities including student interest and facilities and infrastructure. So the purpose of this study is to describe how the interest of students and the condition of facilities and infrastructure in the implementation of table tennis extracurricular activities at Nurul Falah High School Pekanbaru City. This research is a descriptive study that aims to describe the interests of students and the condition of facilities and infrastructure in the implementation of table tennis extracurricular activities at SMA Nurul Falah Pekanbaru City. The population in this study were all students of SMA Nurul Falah Pekanbaru City, amounting to 176 people. The sampling technique is proportional random sampling, which is taking 25% from each local, so there are 30 students as a sample. Data collection in this study was carried out by distributing questionnaires. The data was processed using the Sudjana frequency tabulation. From the analysis of the research results, it can be illustrated that students' interest in participating in table tennis extracurricular activities at Nurul Falah High School Pekanbaru City is 52%, and the condition of facilities and infrastructure can be described as 58% towards the implementation of table tennis extracurricular activities at Nurul Falah High School Pekanbaru City. For this reason, it is hoped that the attention of all parties so that the implementation of extracurricular activities goes well and in accordance with what is expected. Key Words: Table Tennis Extracurricular Activities